Optimalisasi Waktu Pengerjaan Proyek Ruko Dengan Metode Diagram Preseden - Nilwan Andiraja; Rian Rian (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2015)
This research describes the optimization of the overall project timeline store using diagrams precedent method, the case study is project of store in PT. Odrimari Riau Pratam . The objective of this optimization is to accelerate the development of the project and predict the duration project to the structure 1. By determining the constraints and inside there are overlapping activities. Constraints contained in this diagram precedent method is constrained finish to start (FS), constraints begin to start (SS), constraints finished to finished (FF) and constraints start to finish (SF). Then, analysis with forward calculation and backward calculation and determine critical path. Base on analysis, the project of store is finish to the first structure in the prediction will be completed within 130 days when using precedent diagrams methood with the critical path for the project is . In this project there are non-critical activity is B, M and P not fulfilling condition to be a critical activity.Keywords: Constrain, Critical, Optimization, Precedent,Ttime